2015
DOI: 10.1080/15548627.2015.1075688
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-mediated autophagy prevents apoptosis by degrading BBC3/PUMA

Abstract: Abbreviations: BBC3/PUMA, BCL2 binding component 3; BCL2L11/BIM, BCL2-like 11; CA, constitutively active; CDKN1A/ p21, cyclin-dependent kinase inhibitor 1A (p21, Cip1); CHUK/IKKa, conserved helix-loop-helix ubiquitous kinase; CMA, chaperone-mediated autophagy; CHX, cycloheximide; DOX, doxorubicin; IKBKB/IKKb, inhibitor of kappa light polypeptide gene enhancer in B-cells, kinase b; HSPA8/HSC70, heat shock 70kDa protein 8; LAMP2A, lysosomal-associated membrane protein type 2A; NFKB1/NF-kB, nuclear factor of kapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 40 publications
0
45
0
Order By: Relevance
“…Furthermore, the relative expression of HSPA8 mRNA was increased in the cells transfected with anti‐miR‐26b‐5p, but was decreased in HuH7 cells overexpressing miR‐26b‐5p (Figure B). BBC3 is a proapoptotic protein, which is known to be post‐translationally regulated by HSPA8 . While there was no significant difference in the expression of BBC3 at the mRNA level (Figure C), the expression of BBC3 protein was markedly reduced in the HuH7 cells wherein miR‐26b‐5p expression was suppressed (Figure D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the relative expression of HSPA8 mRNA was increased in the cells transfected with anti‐miR‐26b‐5p, but was decreased in HuH7 cells overexpressing miR‐26b‐5p (Figure B). BBC3 is a proapoptotic protein, which is known to be post‐translationally regulated by HSPA8 . While there was no significant difference in the expression of BBC3 at the mRNA level (Figure C), the expression of BBC3 protein was markedly reduced in the HuH7 cells wherein miR‐26b‐5p expression was suppressed (Figure D).…”
Section: Resultsmentioning
confidence: 99%
“…Silencing of miR‐26b‐5p increased the EpCAM+ cell population as well as the expression of both EpCAM and HSPA8 transcripts. This was further accompanied by increased expression of stemness genes which are direct targets of EpCAM and reduced level of proapoptotic protein BBC3 which is known to be degraded by HSPA8 mediated autophagy …”
Section: Discussionmentioning
confidence: 99%
“…In consideration of the declining apoptosis induced by radiotherapy, we thought there must exist some factors to reduce the irradiation-induced apoptosis. Studies showing that CMA pathway activation plays a role in regulating cancer cell proliferation or apoptosis gave rise to our attention[21]. To determine whether CMA pathway activation impacts on the irradiation-induced cancer cell apoptosis, we firstly detected the activation of the CMA pathway.…”
Section: Resultsmentioning
confidence: 99%
“…49,50 It is reported that acetylation, phosphorylation and ubiquitylation are crucial for autophagy induction, regulation and fine-tuning. 33,34,51 We presently indicate that HSD17B4 acetylation at K669 stimulates its degradation via CMA, a selective degradation for proteins, especially those with a long-half-life.…”
Section: Discussionmentioning
confidence: 99%